2016
DOI: 10.1016/j.foreco.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, functional structure and functional redundancy of woodland plant communities: How do mixed tree species plantations compare with monocultures?

Abstract: Managing forest plantation stands in a way that retains productivity targets, but that also fosters biodiversity and stand resilience are key sustainable forest management goals. Current forestry policy advocates a diversification of forest stands to achieve these goals, favouring mixed age structures and polycultures over single-aged monocultures. Evidence is lacking, however, to support this management recommendation for biodiversity gains and related ecosystem service delivery. We used indices of taxonomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Our map revealed 91 cases that reported ecological outcomes of nature‐based interventions in addition to effectiveness in reducing a climate impact. Of these, most had positive outcomes, such as an increased number of species, functional diversity, or higher plant or animal productivity (e.g., Barsoum et al., 2016; Biel, Hacker, Ruggiero, Cohn, & Seabloom, 2017; Liquete, Udias, Conte, Grizzetti, & Masi, 2016). Moreover, 47 of these positive cases also reported benefits to address one or more climate impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Our map revealed 91 cases that reported ecological outcomes of nature‐based interventions in addition to effectiveness in reducing a climate impact. Of these, most had positive outcomes, such as an increased number of species, functional diversity, or higher plant or animal productivity (e.g., Barsoum et al., 2016; Biel, Hacker, Ruggiero, Cohn, & Seabloom, 2017; Liquete, Udias, Conte, Grizzetti, & Masi, 2016). Moreover, 47 of these positive cases also reported benefits to address one or more climate impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of older, larger and well-connected Q. ilex stands in agricultural areas is essential for specialist insects and biodiversity in general (Ruiz-Carbayo et al 2016). This is also important in forest plantations, in which finding a balance between productivity and biodiversity is a key goal in management (Barsoum et al 2016). Quercus suber decline can alter soil respiration and nutrients having effects in other successional forest species and implying vegetation shifts (Ávila et al 2016;Ibáñez et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic map of 376 peer‐reviewed studies (Chausson et al, 2020) showed that most (73%) of the 91 cases that reported on ‘ecological outcomes’ showed benefits, such as an increased number of species, functional diversity, or higher plant or animal productivity (e.g. Barsoum et al, 2016; Liquete et al, 2016) with only 1% showing exclusively negative effects, and 24% reporting mixed or unclear effects. Of the cases with positive ecological outcomes, 47 were reported to also have benefits for adaptation (none were negative, four were mixed).…”
Section: Potential Pitfalls Of Nature‐based Solutionsmentioning
confidence: 99%